The Content, Purification Degree, and Molecular Weight of Inulin of Natural Dangshen Roots (Codonopsis javanica) in Highland Lam Vien, Vietnam - Nguyễn, Thị Thăng Long (2022)
Introduction: Inulins are a group of natural active polysaccharides found in ginseng and Dangshen and are mainly used in pharmaceutical preparations and functional food. The purification condition of inulin from Dangshen grown in Vietnam did not occur in previous studies. Hence, the study presented the content, purification degree, molecular weight, and functional group characteristics of inulin extracted from natural Dangshen roots (Codonopsis javanica) in other purification conditions. Methods: Some factors survey impact purification conditions of inulin, for example, the kinds and the concentration of the solvent, the temperature and the times of the precipitation, and the active coal impact. The objects such as the content of inulin, fructan, and crude polysaccharide, purification degree of inulin, and fructan were analyzed. Molecular weight and functional group characteristics of purification inulin extracted from Dangshen roots (Codonopsis javanica) grown in highland Lam Vien, Vietnam, were also analyzed. Results: The purification degree of inulin purified by using ethanol was higher than that using active coal, corresponding to 97.85a ± 0.84 % and 94.05 %, respectively. Inulin content was the large ratio in crude polysaccharides, exhibited via FTIR and the analysis results. Inulin and fructan were the most precipitated in ethanol, for example, 80 % and 90 % ethanol, respectively, compared to another solvent. The kind and the concentration of the solvent, the temperature and the precipitation times, and active coal impacted the content and the purification degree of inulin and fructan (p < 0.05). The precipitation of inulin and fructan in ethanol solvent was affected by the temperature. The molecular weight of inulin and fructan corresponded to 3,193 Da and 1,112,892 Da, respectively. Conclusion: Inulin of natural Dangshen roots in Lam Vien highland, Vietnam was useful for functional foods and pharmaceutics.